Variation in Preoperative and Postoperative Physical Therapist Management of Patients Opting for Elective Abdominal Surgery. Issue 10 (25th July 2019) - van Beijsterveld, Christel A; Heldens, Aniek F; Bongers, Bart C; van Meeteren, Nico L
Abstract: Background: Evidence about the role of physical therapy in perioperative care pathways to improve postoperative outcomes is growing. However, it is unclear whether research findings have been translated into daily practice. Objective: The objectives of this study were to describe the current content and between-hospital variability of perioperative physical therapist management for patients undergoing colorectal, hepatic, or pancreatic resection in the Netherlands and to compare currently recommended state-of-the-art physical therapy with self-reported daily clinical physical therapist management. Design: This was a cross-sectional survey study. Methods: Hospital physical therapists were asked to complete an online survey about pre- and postoperative physical therapy at their hospital. To explore the variability of perioperative physical therapist management between hospitals, frequency variables were clustered to determine the level of uniformity. Latent class analysis was performed to identify clusters of hospitals with certain homogeneous characteristics on a 19-item dichotomous scale. Results: Of 82 eligible Dutch hospitals, 65 filled out the survey (79.3%). Preoperative physical therapy was performed in 34 hospitals (54.0%; 2/65 responding hospitals were excluded from the data analysis). Postoperative physical therapy was performed in all responding hospitals, focusing mainly on regaining independent physical functioning. Latent class analysis identified a 3-class model. Hospitals in classes I and II were more likely to provide preoperative physical therapist interventions than hospitals in class III. Limitations: The use of self-reported answers can lead to bias. Conclusions: There was a wide degree of variability between hospitals regarding pre- and postoperative clinical physical therapist practice for patients opting for major abdominal surgery. Three different classes of daily practice were identified. Further translation of key research findings into clinical physical therapist practice is advised, especially for hospitals in which the physical therapist is not involved preoperatively. Moreover, improving uniformity by developing up-to-date clinical guidelines is recommended.